MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA SISWA SD MELALUI MODEL PEMBELAJARAN MAKE A MATCH - Dewi Candra (IKIP Siliwangi, 2019)
This research was motivated by the low ability to solve mathematical problems in elementary school students. This study goal to determine the achievement and improvement of mathematical problem solving skills in elementary school students through the make a match learning model. The research method used was quasi-experimental with pretest and posttest design. The population in this research were all fourth grade students at CIBEBER SDN 4. The selected sample was class IV A as the control class using conventional learning models and class IV B as the experimental class using the make a match learning model with a total of 60 students. Score data pretest, posttest, and N-Gain were analyzed using the normality test, homogeneity test, and test the difference in the two averages using SPSS 23. The results of the score data analysis were two differences in the average results of Mann-Whitney test data analysis N-Gain data where the value significance of 0,448. This value is greater α means that proven learning model make a match can improve mathematical problem solving skills. AbstrakPenelitian ini dilatarbelakangi kurangnya kemampuan pemecahan masalah matematika pada siswa SD. Penelitian ini bermaksud untuk mengetahui pencapaian dan peningkatan keterampilan penyelesaian masalah matematika pada siswa SD melalui gaya pengajaran make a match. Metode observasi yang dipakai adalah kuasi eksperimen dengan desain pretes dan postes. Populasi dalam riset ini adalah semua peserta didik kelas IV di SDN CIBEBER 4. Sampel yang dipilih yaitu tingkat IV A sebagai grup kontrol memakai jenis pembelajaran konvensional dan kelas IV B sebagai kelas percobaan menggunakan model pengajaran make a match dengan total 60 orang siswa.. Data nilai pretes, postes, dan N-Gain dianalisis dengan menggunakan uji normalitas, uji homogenitas, dan tes perbedaan dua rata-rata menggunakan SPSS 23. Hasil telaah data skor perbedaan dua rata-rata hasil pengolahan data uji Mann-Whitney data N-Gain dimana nilai signifikansi sebesar 0,448. Angka tersebut lebih besar α artinya terbukti model pembelajaran make a match dapat menambah kemampuan pemecahan masalah matematika.